Structural and optical properties of rare earth nano-crystalline oxides embedded in polymethyl methacrylate - (:unkn) unknown (TechConnect, 2016)
In this study, various sizes of rare earth oxide nano-crystalline powders (Nd2O3 and Er2O3) were doped into polymethyl methacrylate (PMMA) host material which were synthesized using the thermal decomposition method. The structural characterization of the composites were made using X-ray diffraction. The spectroscopic measurements such as absorption and emission spectra were conducted. PMMA is an amorphous, thermoplastic polymer with an optical transparency region from 300 nm to 2800 nm. Beyond the excellent optical properties, PMMA shows superior resistance to laser, high mechanical strength and ease of synthesis thus, this properties make it suitable for the production of elastic polymer material that emits light.
Keywords: Absorption; Emission; PMMA; Rare earth oxides; XRD